Anomalous Left Coronary Artery Connected to the Pulmonary Artery in a 15-Year-Old Girl: Case Report and Discussion on Secondary Prevention of Sudden Death. (1st September 2021) - Laïk, Jérémy; Fouilloux, Virginie; Aldebert, Philippe; Koutbi, Linda; Hourdain, Jérôme; De Swardt, Philippe; Tiger, Fabrice; Bellemain-Appaix, Anne; Bernasconi, François; Jacq, Laurent
Abstract : Background . Anomalous left coronary artery connected to the pulmonary artery (ALCAPA) is a rare congenital heart disease. Adaptive development of sufficient heterocoronary collaterality in the newborn may allow survival to a later age. In older children or adults, malignant ventricular arrhythmias can reveal the disease. Case Report . A 15-year-old girl was referred to the local hospital after a resuscitated out-of-hospital cardiac arrest. CT scan and coronary angiography revealed an ALCAPA. Direct aortic reimplantation of the left coronary artery was performed. Postoperative ECG monitoring showed short episodes of nonsustained ventricular tachycardia. Transthoracic echocardiography and cardiac MRI revealed subendocardial fibrosis of the anterolateral papillary muscle. Beta-blockade therapy was initiated at first intention. After hospital discharge, the patient reported several fainting without loss of consciousness. Considering sudden death nonrelated to effort, episodes of nonsustained ventricular tachycardia, and areas of myocardial fibrosis, the patient underwent subcutaneous cardioverter-defibrillator implantation. 6-month follow-up is satisfactory without clinical or rhythmic abnormalities. Discussion . Indication for surgical correction of ALCAPA is well defined, but rhythmic secondary prevention after resuscitated cardiac arrest is less consensual. Cardiac MRI is an essential tool in the identification of a potential rhythmic substrate and should be taken into account in the discussion of a preventive cardioverter-defibrillator implantation.